Comparison of growth indices between patients with treated congenital hypothyroidism and healthy children in the Kurdish population: a historical cohort study - Arabzadeh, Behnam; Hajizadeh, Nazanin (Researcher Bulletin of Medical Sciences, 2021)
Objective: Congenital hypothyroidism (CH) refers to a condition in which there is a low level of thyroid hormone in an infant’s blood. It can result in serious problems in physical and mental development of patients. This study aimed to compare growth indices in patients with and without CH. Materials and Methods: Historical cohort study, 96 patients with CH in different counties of Kurdistan province were considered as exposed cases. The non-exposed group included children of the same age, sex and geographical area as much as possible. Independent t-test was used to compare growth indices in the two groups. Moreover, repeated measurement was used to compare the two groups in terms of trend of changes in growth. Results: There was a significant difference between the two groups of neonates in terms of weight and head circumference measured at third and ninth months of ages (p<0.05) respectively. Moreover, no statistically significant difference was observed between the two groups in terms of the trend of changes in growth percentiles (head circumference, height, and weight) (p>0.05). Conclusion: The quality of care provided for CH patients in Kurdistan province is at a desirable level.